A series of four novel alkaline earth metal-organic frameworks constructed of Ca(ii), Sr(ii), Ba(ii) ions and tetrahedral MTB linker: structural diversity, stability study and low/high-pressure gas adsorption properties - Almáši, Miroslav; Zeleňák, Vladimír; Gyepes, Róbert; Zauška, Ľuboš; Bourrelly, Sandrine (RSC advances, 2020)
A series of four novel microporous alkaline earth metal-organic frameworks (AE-MOFs) containing methanetetrabenzoate linker (MTB) with composition {[Ca4(μ8-MTB)2]·2DMF·4H2O} n (UPJS-6), {[Ca4(μ4-O)(μ8-MTB)3/2(H2O)4]·4DMF·4H2O} n (UPJS-7), {[Sr3(μ7-MTB)3/2]·4DMF·7H2O} n (UPJS-8) and {[Ba3(μ7-MTB)3/2(H2O)6]·2DMF·4H2O} n (UPJS-9) (UPJS = University of Pavol Jozef Safarik) have been successfully prepared and characterized. The framework stability and thermal robustness of prepared materials were investigated using thermogravimetric analysis (TGA) and high-energy powder X-ray diffraction (HE-PXRD). MOFs were tested as adsorbents for different gases at various pressures and temperatures. Nitrogen and argon adsorption showed that the activated samples have moderate BET surface areas: 103 m2 g-1 (N2)/126 m2 g-1 (Ar) for UPJS-7'', 320 m2 g-1 (N2)/358 m2 g-1 (Ar) for UPJS-9'' and UPJS-8'' adsorbs only a limited amount of N2 and Ar. It should be noted that all prepared compounds adsorb carbon dioxide with storage capacities ranging from 3.9 to 2.4 wt% at 20 °C and 1 atm, and 16.4-13.5 wt% at 30 °C and 20 bar. Methane adsorption isotherms show no adsorption at low pressures and with increasing pressure the storage capacity increases to 4.0-2.9 wt% of CH4 at 30 °C and 20 bar. Compounds displayed the highest hydrogen uptake of 3.7-1.8 wt% at -196 °C and 800 Torr among MTB containing MOFs.